JOINT EFFORTS OF THE MEDIA, CIVIL SOCIETY AND THE STATE TO COUNTER RUSSIAN DISINFORMATION - Piskorska, Galyna; Ryzhova, Daria; Yakovets, Anatoly (International Journal of Innovative Technologies in Social Science, 2023)
The article deals with the problems of institutional support of information security in the context of the full-scale war between Russia and Ukraine. The strategies and tools used by the Ukrainian state and civil society in the field of information policy to counter disinformation have been studied. Global awareness of the need to counter the hostile narratives used by Russia against Ukraine and the West is a real way out of the threatening situation caused by massive Russian disinformation campaigns. Disinformation cannot be defeated solely by closing channels or social media pages. Success requires the joint efforts of the media, public organizations, and the state. The authors of the article conclude that the most effective strategy for countering disinformation should be based on a combination of technological techniques for removing unwanted content and ensuring the dominance of the dominant mainstream narratives of the state in its own information space and in the information space of foreign countries. The authors have carried out the research on the resistance of the young generation of Ukrainians to disinformation and determined Ukraine's goals in the information war.